2020
DOI: 10.1016/j.cell.2020.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Induced Type I Interferons Instruct a Poised Basal State of Dendritic Cells

Abstract: Environmental signals shape host physiology and fitness. Microbiota-derived cues are required to program conventional dendritic cells (cDCs) during the steady state so that they can promptly respond and initiate adaptive immune responses when encountering pathogens. However, the molecular underpinnings of microbiota-guided instructive programs are not well understood. Here, we report that the indigenous microbiota controls constitutive production of type I interferons (IFN-I) by plasmacytoid DCs. Using genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
170
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(179 citation statements)
references
References 87 publications
8
170
0
1
Order By: Relevance
“…TLR3 is most expressed in the carotid arteries and aorta, TLR7 in the iliac and carotid arteries, and TLR9 with overall low expression but most prominent expression in the iliac arteries 28 TLR 2,3,4,7, and 9 stimulation have been implicated in the development of atherosclerosis through combination of promoting of lipid uptake into the plaques, monocyte activation, endothelial dysfunction, and foam cell formation 29 34 . Recently TLR2 has been shown to facilitate microbiota-induced VWF expression and systemic interferon responses mice 35 , 36 . Our data suggest Lp299v may reduce inflammation in part through reducing TLR activation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…TLR3 is most expressed in the carotid arteries and aorta, TLR7 in the iliac and carotid arteries, and TLR9 with overall low expression but most prominent expression in the iliac arteries 28 TLR 2,3,4,7, and 9 stimulation have been implicated in the development of atherosclerosis through combination of promoting of lipid uptake into the plaques, monocyte activation, endothelial dysfunction, and foam cell formation 29 34 . Recently TLR2 has been shown to facilitate microbiota-induced VWF expression and systemic interferon responses mice 35 , 36 . Our data suggest Lp299v may reduce inflammation in part through reducing TLR activation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although accumlated evidences has shown that microbiota can promote ISG responses in multiple cell types, the cellular sources of type I IFN are yet less-well defined until very recently, where two papers demonstrated that microbiota constitutively induces type I IFN production and basal level of ISG expression in pDCs at systemic sites [17,18]. In our study, we only looked at the frequency of pDCs in PBMC or spleen following EMCV infection at 3 dpi, and observed no differences between PBS and Abx mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two compelling back-to-back research articles reported that plasmacytoid dendritic cells (pDCs) are the main cellular sources of Microbiota-induced IFN-I. Schaupp and colleagues demonstrated that microbiota-driven IFN-I expression by pDCs primes conventional dendric cells (cDCs) to initiate immune responses following pathogen encounter [17]. Meanwhile, Diamond's group has pointed out that IFN-I produced by microbiota-enabled pDCs prevents alphavirus, Chinungunya virus (CHIKV) in particular, from infection and dissemination in host blood monocytes [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that heterozygous carriers of the p.Pro193ala allele produce slightly elevated levels of type-I IFNs to better deal with viral insults. Genetic lesions resulting in subclinically elevated type-I IFN levels may thus supplement the microbiotadriven tonic type-I IFN response and prime the immune system for future infections (Abt et al, 2012;Bradley et al, 2019;Ganal et al, 2012;Schaupp et al, 2020;Steed et al, 2017;Winkler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%